Mechanization in Pigeon pea – Scope and Opportunities in India - Ramanjaneyulu, A. V.; Sravanthi, D.; Swetha, D.; Sainath, N.; Madhu, M.; Kumar, C. V. Sameer; Reddy, B. Sanjeeva (Chronicle of Bioresource Management, 2021)
Pigeon pea is the second most important pulse crop next to chickpea in India. It is grown widely under rainfed conditions across tropical and sub-tropical regions of the World. Declining work force, increasing labour and production cost in Agriculture are necessitating introduction of mechanization in every crop and pigeon pea is not an exception to this. Mechanization minimizes use of labour and envisages utilization of various user friendly tools and farm machinery either partially or completely to perform various agronomic operations starting from pre-sowing to post harvest operations. We have discussed in this article the scope and opportunities available for achieving complete mechanization in sole as well as intercropped pigeon pea in India.